2004
DOI: 10.1097/01.sla.0000137128.64978.bc
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Benign and Malignant Thyroid Nodules by Molecular Profiling

Abstract: Molecular profiling readily distinguishes between benign and malignant thyroid tumors with excellent sensitivity and specificity. Elucidated genes may provide insight into the molecular pathogenesis of thyroid cancer. Gene profiling may significantly enhance the evaluation of thyroid nodules in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 43 publications
6
99
1
2
Order By: Relevance
“…Such a failure could be explained by the great similarity in overall gene expression profiles observed between the 2 sample groups, as demonstrated by Figures 1 and 2, which may be further indication that the 2 lesions are similar not only phenotypically but also at the level of gene expression. Our data are in disagreement with those published previously by Finley et al and by Barden et al, [11][12][13] who identified a set of genes that, by clustering algorithms, could distinguish between adenomas and follicular carcinomas. This discrepancy may be explained by the number and identity of the genes present in our arrays compared with the arrays used by other groups or by differences in mathematical and statistical approaches.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Such a failure could be explained by the great similarity in overall gene expression profiles observed between the 2 sample groups, as demonstrated by Figures 1 and 2, which may be further indication that the 2 lesions are similar not only phenotypically but also at the level of gene expression. Our data are in disagreement with those published previously by Finley et al and by Barden et al, [11][12][13] who identified a set of genes that, by clustering algorithms, could distinguish between adenomas and follicular carcinomas. This discrepancy may be explained by the number and identity of the genes present in our arrays compared with the arrays used by other groups or by differences in mathematical and statistical approaches.…”
Section: Discussioncontrasting
confidence: 57%
“…Using oligonucleotide arrays, Finley et al identified differentially expressed genes among carcinomas, adenomas, and hyperplastic nodules; and the expression of those genes was used to cluster samples that represented different pathologies. 11,12 A similar technique was employed in the comparison of follicular carcinomas and adenomas and demonstrated different profiles after hierarchical clustering. 13 Recently, we described the identification of molecular classifiers that could distinguish between malignant and nonmalignant lesions of the gastric mucosa.…”
mentioning
confidence: 99%
“…Genes regulated in a similar direction in cultured thyrocytes and autonomous adenomas, but that are regulated in the inverse way in papillary carcinomas, might reflect the differentiating action of the TSH-cAMP pathway [DIO2 (26,37), HGD (38), FHL1 (39), ITPR1 (39,40), CRABP1 (40,41), and ADM (40)], whereas common expression in the TSH-stimulated thyrocytes, autonomous adenomas, and papillary carcinomas concerns possibly proteins involved in the control or support of cell growth [EFHD2, IER2, KLF6 (10), EGR1 (10), GADD45B, and JUN]. One puzzling common property of autonomous adenomas and papillary carcinomas is the down-regulation of a number of immediate early genes [NR4A1, JUNB (10), KLF10, and ZFP36].…”
Section: Discussionmentioning
confidence: 99%
“…Distinctive gene expression patterns are associated with a wide variety of morphological, biological and clinical parameters. This approach has now begun to be applied to thyroid cancer (Huang et al, 2001;Finley et al, 2004;Giordano et al, 2005;Jarzab et al, 2005;Eszlinger et al, 2006). Although some studies have included FVPTCs and minimally invasive FTCs, none has examined the challenging group of tumours of uncertain malignancy (T-UM).…”
Section: Introductionmentioning
confidence: 99%